(untitled) (Research, Society and Development, 2020)
Due to early tooth loss, alveolar resorption goes throughout life, as well as a size reduction of the alveolar ridge. The loss of bone height leads to the flattening of the palate, this leads to maxillary sinuses pneumatization along with the expansion of their chambers, a factor that hinders the success in fixing implantable elements. This study aims to report a case of a patient who underwent surgery to lift the maxillary sinus and install implants in the posterior area of the maxilla (absence of elements 15 and 16). The Sinus Lift technique was chosen following the indication based on the height of the residual bone, which was 4mm. With the displacement of the sinus membrane and the filling of the cavity with xenogenous bone graft Bio-Oss large 1g done, a simultaneous installation of the Neodent Gran Morse 3.5 implants. x11.5 were performed. After the procedures, a period of 6 months will be waited for final rehabilitation with the fixed prosthesis on the implants. This reduction in time for rehabilitation is one of the positive aspects of this simultaneous technique.